Enhancing the functional characteristics of soy protein isolate via cross‐linking catalyzed by Bacillus subtilis transglutaminase. (13th January 2021) - Liu, Yexue; Zhang, Yuanfu; Guo, Zehui; Wang, Chen; Kang, Hongwei; Li, Jingwen; Wang, Wenhang; Li, Yu; Lu, Fuping; Liu, Yihan
Abstract: BACKGROUND: Although Streptomyces mobaraense transglutaminase (MTG) has been extensively applied to enhance the functional characteristics of soy protein isolate (SPI) through cross‐linking, various transglutaminases (TGs) in nature may provide more choice in the food industry. Previous research reported that TG derived from Bacillus subtilis (BTG) exhibited better pH stability and thermostability than MTG. RESULTS: An attempt was made to study the influence of BTG induced cross‐linking on the properties of SPI. Sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS–PAGE) results indicated that almost all protein constituents ( α ', α, β, AS, and BS) in SPI could be cross‐linked with BTG treatment. The BTG treatment also resulted in a significant increase (* P < 0.05) in SPI mean particle size. Emulsifying activity and stability were improved from 0.11535 m 2 g −1 and 48.3% for native SPI to 0.13252 m 2 g −1 and 83.9% for SPI treated with BTG at 6 h. Similarly, the modified SPI showed better foam activity (1.32 mL) and stability (87.6%) than the original SPI (0.93 mL and 56.8%). The water‐holding capacity of SPI gel was found to increase with time, with a value of 95.43% at 6 h. Furthermore, SPI gel's texture profiles were greatly improved by adding BTG (* P < 0.05). CONCLUSION: The results of the present study indicated that BTG could be a promising cross‐linking agent for improving the functional characteristics of SPI. As a substitute for MTG, BTG could thus potentially be used for food structure engineering to enhance the functional characteristics of multiple proteins to advance the development of food chemistry. © 2020 Society of Chemical Industry